Populism in Muslim democracies and its absence - Mohamad Shukri, Syaza Farhana (2019)
Populism throughout the world has been on the rise especially in the second decade of the twenty-first century. From the United States of America to its cousin in the Philipines, populist leaders have used the veneer of a national crisis to legitimize a leadership that dignifies a section of the population over the elite establishment and the various bureaucratic institutions of the past. While further enfranchisement is to be applauded, populist leaders rile up people’s emotions over rational discussion on policy making. This combination could lead to terrible consequences to “the others” who may not subscribe to the beliefs of the populist leaders. Populism is the result of years of economic mismanagement that have led to great disparity between the “haves” and “have nots”. The interesting question for us now is to consider why is it that despite this global rise in populism, there is only two Muslim populists currently in power (among a group of 20). This research aims to discover the phenomenon of populism in Muslim democracies such as Indonesia and Turkey, and to understand reasons for its relative absence in Tunisia and Malaysia. In order to create a sustainable world order that does not further inflame dangerous populist rhetoric, it is crucial for us to understand ways to ward off the spread of populism especially in Muslim countries with their nascent democracies that are susceptible to such rhetoric.